Carex ×payettei, a new hybrid of Carex sect. Racemosae described from subarctic Quebec, Canada (Cyperaceae) - Cayouette, Jacques; Léveillé-Bourret, Étienne (Phytotaxa, 2021)
A new hybrid is described between two boreal species of Carex sect. Racemosae, the North American Carex atratiformis and the circumboreal Carex media, under the name of Carex ×payettei. It is reported in Nunavik (Northern Quebec, Canada), in nine localities within the Forest Tundra and Open Boreal Forest zones. It is intermediate in morphology between the parental species and is not completely sterile, frequently producing fruits. Pollen stainability of the hybrid varied between 10% and 37% while its parents display values above 95%.